Multi-Criteria Decision Making Using TOPSIS Method: An Application in the Selection of Future Communication Solutions for Electrical Distribution Substations - Mohd Azmi K.H.; Asyikin Mohamed Radzi N.; Mohamed Yusop N.Y.; Zaini Jamaludin M.; Abdullah F.; Ismail A.; Samidi F.S.; Adriana Azhar N.; Zulkifli I.T.; Muhammad Zainal A. (IEEE Computer Society, 2023)
Electric substations; Communication technology selection; Communicationtechnology; Electrical distribution networks; Multi criteria decision-making; Multicriteria decision-making; Multicriterion decision makings; Solution methods; Technique for order preference by similarities to ideal solutions; Technique for order preference by similarity to ideal solution method; Technology selection; Decision making